Strengthening the Role of Community Health Workers in High Stunting Prevalence Areas of Kendari City, Southeast Sulawesi Province, Indonesia: A Qualitative Study - Bahar, Hartati; Effendy, Devi Savitri; Lestari, Hariati (YCAB Publisher, 2025)
Background: The role of posyandu (integrated health post) cadres constitutes a critical pillar in accelerating stunting reduction efforts in Indonesia. Nevertheless, in practice, their contribution is often perceived as supplementary within primary healthcare services. Objective: This study aims to conduct an in-depth analysis of the strengths of posyandu cadres in assuming an active role in stunting reduction efforts in the stunting locus area of Dapu-dapura Village. Methods: This qualitative study employed three data collection techniques: focus group discussions (FGDs), in-depth interviews, and direct observations. Two FGD sessions were conducted, and interview transcripts were analyzed using content analysis. Informants included posyandu cadres, healthcare workers, mothers of stunted children, and local government representatives. A total of 16 participants aged 28 to 63 years were involved. Results: The findings indicate that elderly cadres (60+ years) possess greater experience and employ interpersonal approaches that are more readily accepted by the community than younger cadres. These senior cadres have effectively shifted maternal perceptions related to stunting stigma, particularly among those hesitant to attend posyandu. They serve as key intermediaries connecting healthcare workers responsible for program implementation with mothers as service users. Strategic efforts are needed to prepare younger cadres to gradually assume these roles as part of cadre regeneration. Conclusion: Posyandu cadres in Dapu-dapura Village play an essential intermediary role in stunting prevention; however, their performance is constrained by social stigma, limited maternal nutritional literacy, and geographic barriers. Strengthening competencies in management, measurement accuracy, and counseling is necessary to enhance their effectiveness in contributing to stunting reduction at the community level.